Advances in plasmon‐enhanced upconversion luminescence phenomena and their possible effect on light harvesting for energy applications. Issue 6 (17th August 2017) - Khan, M.A.; Idriss, H.
Abstract : The focus of the review is on the recent advances of inorganic materials used for upconversion luminescence as well as the effect of plasmonic metals on the efficiency of the overall system. Central to the review is the effect of these upconverting luminescence materials coupled with plasmonic metals on photovoltaic cells and photocatalysts performance. The diffuse nature of sun light on earth (low flux) and its weak energy (low frequency) are the main hurdles for practical applications related to energy‐intensive processes. Upconversion luminescence materials increase light energy (high frequency) with weak efficiency, and when combined with plasmonics (potentially providing high local light flux), the overall efficiency of the system can be improved. Examples in this review are exclusively based on lanthanide compounds as light‐converting devices and on Au and Ag as plasmonic metals. Due to the so called 'lanthanides contraction, ' the f ‐orbitals of lanthanide cations are shielded from the outside environment (chemical bonds) when compared to early transition metals. This and the many energy levels associated with these f ‐orbitals make them (particularly the Ln 3+ 4 f 10, 4 f 11, 4 f 12, and 4 f 13 ) the most suitable materials for multiple energy transfer systems so far. While upconversion luminescence was first observed over half a century ago, since the pioneering work of Auzel, coupling it with plasmonics has only attracted attention in the last few years, and a limited amount of work is currently available. This review has compiled representative work in the field with the aim to motivate researchers to exploit this concept, which is central to light–matter interaction, and its effect on chemical reactions relevant to energy and the environment. WIREs Energy Environ 2017, 6:e254. doi: 10.1002/wene.254 This article is categorized under: Energy Research & Innovation > Science and Materials Abstract : A Schematic representation of a wide band gap semiconductor catalyst coated on top of plasmon‐upconverter material. The catalyst can only absorb UV portion of sunlight. A large fraction of sunlight in the visible and IR penetrates the catalytic material, interacts with the plasmonic material and is thus amplified. This amplified light is then converted to high energy photons by the upconverting material that can back excite the semiconductor increasing the light harvesting efficiency. B: Absorption and emission spectra of up converting nanocrystals. These materials are generally comprised of an inert host material (often NaYF4) doped with sensitizer (such as ytterbium, Yb 3+ ) and activator (Thuluim, Tm 3+ ) lanthanide ions. Yb 3+ ions are excited by a 980 nm light is conveniently resonant with the f–f transitions of Tm 3+, facilitating efficient energy transfer leading to upconversion emission bands at 345, 365, 451, 481, 646, and 800 nm.